HUBUNGAN ANTARA LIKUIDITAS, PENDANAAN DENGAN MANAJEMEN PERKREDITAN KSP DANATAMA JAKARTA - Bambang Wahyudiono (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2019)
Research have been done based on KSP management and KSP performance. Problem loan increased in some KSP. The study proposed to further explore why this condition happened by analysis relationship between performance loan management, liquidity and funding. Research result presents liquidity rate of entity 68,81% as expected, funding rate 64,23% as expected and Loan management rate of the entity is 65,05% as expected. Result of result also present that the rate of three variables still under value as expected (more than 80%) thatswhy still need to be improve. Correlation rate between liquidity and loan management is 0,212, determination coefficient is 0,0449 or giving impact more or less than 4,49%. There is no correlation between Funding and loan management (rate is -0,0276). T-calculate is less than T-table. Correlation rate between liquidity, funding and loan management simultaneously is 0,093. This shows that liquidity factor together with funding factor giving impact to loan management more significant than partially. Impact of the two variables is 9,3%. As a result, to increase loan management rate will be more effective if increasing liquidity rate and funding rate to be implemented together other than partially instead.